Cumulation of Lawsuits Between Administrative Decisions and Factual Actions in Administrative Court Decisions - Pasaribu, David; Silalahi, Irene Cristna; Purba, Selviana (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2025)
The concept of Administrative Decisions (KTUN) has evolved considerably since the promulgation of the Government Administration Law (AP Law), especially with the broadening of disputed objects to cover governmental actions. This change was further reinforced by Regulation of Supreme Court Number. 2 of 2019, transferring jurisdiction over tort claims against government officials from the GeneralCourts to the Administrative Courts (PTUN). However, its implementation remains challenging, especially regarding the cumulative filing of KTUN and tort lawsuits, remaining unregulated explicitly, as referred to in Supreme Court Decision No. 343 K/TUN/TF/2024 and number 594 K/TUN/TF/2024. The core issues include the ratio legis behind the expanded interpretation of KTUN under AP Law, judicial reasoning in accepting the accumulation of disputed objects and formulating an ideal concept for combining KTUN and factual actions in one claim. This research adopts a normative (doctrinal) method with a casuistic-conceptual approach. The findings indicate that the expansion of KTUN under AP Law aims to enhance legal protection for citizens against administrative actions, promote good governance, ensure governmental accountability, and broaden the supervisory role of PTUN. Supreme Court Decisions Number 343 K/TUN/TF/2024 and Number 594 K/TUN/TF/2024 affirm that cumulative claims involving KTUN and factual actions are permissible when both share a strong legal correlation as part of a single administrative series. The ideal concept of cumulative lawsuits includes close legal relevance, consistency among the object, legal grounds, and claims, support for a swift, simple, and low-cost judicial process, promotion of legal utility, prevention of conflicting rulings, and avoidance of prohibited claim mixing.